Desire for greener land: Options for sustainable land management in drylands - Schwilch, Gudrun; Hessel, Rudi; Verzandvoort, Simone (CTA / Alterra, 2012)
This text intends to support people’s efforts to invest wisely in the sustainable management of land – enabling greener drylands to become a reality. Clearly laid out in a concise and well-illustrated format, it decribes the DESIRE – desertification mitigation and remediation of land – approach and the World Overview of Conservation Approaches and Technologies (WOCAT) methodology. The book includes an analysis of current degradation and sustainable land management (SLM) in DESIRE study sites, and also compiles an assessment of the SLM technologies and approaches trialled in the DESIRE project. Conclusions and policy points are presented for decision-makers, the private sector, civil society, donors and researchers.